Transforming economics values toward life: From heterodoxy to orthodoxy. Issue 1 (12th September 2021) - Waddock, Sandra
Abstract: In the face of numerous crises, including a global pandemic, it is time to challenge economic orthodoxy—neoliberalism—and develop a new economic orthodoxy built around values and principles that give life and prominence to socioecological systems. In this essay, I link six values of life‐affirming economics to principles that give life to systems. The life‐affirming economic values are stewardship of the whole; cocreating collective value; cosmopolitan localist‐governance; regenerativity, reciprocity, and circularity; relationality and connectedness; and equitable markets and trade. These values can be linked to principles that give life to systems, which include wholeness, purpose, boundedness, connectedness and diversity, and human consciousness or awareness. Because humans can design markets and trade to be equitable, if they so desire, all of the principles that give life are linked to that value. Combined these principles provide a platform for a set of assumptions underpinning a potential new economic orthodoxy to replace the flawed set of assumptions in the neoliberal economics currently dominant in industrialized nations.